2011
DOI: 10.1212/wnl.0b013e31822e045c
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid reduces chemotherapy-induced neuropathy in an animal model and patients with lung cancer

Abstract: Objective:To evaluate the effect of all-trans retinoic acid (ATRA) as treatment for chemotherapyinduced peripheral neuropathy in an experimental animal model and in a randomized, doubleblinded, controlled trial in patients with non-small-cell lung cancer (NSCLC). Methods:Forty male Wistar rats were randomized in 5 groups: group A, control; groups B and C, treated with cisplatin; and groups D and E, treated with paclitaxel. ATRA (20 mg/kg PO) was administered for 15 days in groups C and E. We evaluated neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 35 publications
(42 reference statements)
2
41
0
Order By: Relevance
“…Our findings that cisplatin-induced neurotoxicity was associated with histological alteration agreed with the reports of the reports of Al Moundhri et al (2013) and Arrieta et al (2011) who similarly reported this observation. This supported our findings of cisplatin's alteration of the histology of the densely packed layers of granule neurons of the dentate gyrus of the hippocampal formation and the pyramidal neurons of the CA3 zone of the hippocampus proper when compared with the neurons of the control rats.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings that cisplatin-induced neurotoxicity was associated with histological alteration agreed with the reports of the reports of Al Moundhri et al (2013) and Arrieta et al (2011) who similarly reported this observation. This supported our findings of cisplatin's alteration of the histology of the densely packed layers of granule neurons of the dentate gyrus of the hippocampal formation and the pyramidal neurons of the CA3 zone of the hippocampus proper when compared with the neurons of the control rats.…”
Section: Discussionsupporting
confidence: 93%
“…274,275 Furthermore, since embryonic neurons are dependent on NGF for survival, it is difficult to interpret the survival findings, since low concentrations of paclitaxel which alter neuronal sensitivity do not commonly cause neuronal death in cultures of DRG neurons derived from adult animals. 157 Other neurotrophic agents which have been investigated and have had positive results in preclinical animals include: prosaptide, 129 xaliproden, 276 retinoic acid, 277 and recombinant human glial growth factor 2 278 , but so far none have demonstrated appreciable efficacy in clinical trials. 279 Neurotrophic factors play an integral role not only in the survival of sensory neurons but also in the maintenance of the neurons, thus helping to establish the setpoints for neuronal sensitivity and growth.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…Acety-L-Carnitine [65], Alpha-lipoic acid [66], Amifostine [67], cholest-4-en-3-one, oxime (TRO19622) [68], Cannabinoid type-1 receptor [69], Gabapentin [70], Glutamine [71], Lamotrigine [72], recombinant human leukemia inhibitory factor (rhuLIF, AM424, emfilermin) [73], Neurosteroids [74], Palmitoylethanolamide [75] and Retinoic acid [76] were studied individually for their efficacy in randomized clinical trials.…”
Section: Medical Managementmentioning
confidence: 99%